Learning outcomes of the educational board game "Taphonomy: Dead and Fossilized, " evaluated with high school learners in a summertime program. Issue 2 (14th March 2022) - Salgado-Jauregui, Estefanía; Martindale, Rowan C.; Ellins, Katherine; Reyes, Enrique; Weiss, Anna
Abstract: Although many have suggested the use of games to motivate active learning, studies that evaluate the learning outcomes of games with high school students are scarce. Here, we present the evaluation of the board game "Taphonomy: Dead and Fossilized" as an active learning tool to teach fossilization and Earth systems thinking with rising 12 th grade learners in GeoFORCE Texas, a summertime outreach program of the Jackson School of Geosciences, The University of Texas at Austin. The educational activity was evaluated with two groups (n1 = 22, n2 = 27). During the activity, an observation protocol was implemented; prompts to evaluate learners' behaviors and instructor behaviors were included in a form that a trained observer filled out while the learners played the game. Learning outcomes were assessed with a 2-page paper survey immediately following gameplay; survey questions are aligned with the Next Generation Science Standards. "Strategizing" was the most common learner behavior observed during the activity and the majority of behaviors can be considered "active learning". The results from the survey show that after playing the game learners were able to apply paleontological knowledge to tasks that involved establishing cause-effect relationships and Earth systems thinking. Our results provide evidence that board games (as educational strategies) are effective active learning tools that foster student development of scientific skills. Cooperative learning was observed, which we suggest is a key benefit for diverse classrooms. Findings were used to guide the refinement of the high school-level version of "Taphonomy: Dead and Fossilized", as well as a scaffolded teaching module with formative and summative questions for use in a classroom setting.